2017
DOI: 10.1155/2017/4089214
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect and Mechanism of Thiazolidinedione on Dopaminergic Neurons In Vivo and In Vitro in Parkinson’s Disease

Abstract: The aim of the present study was to gain insight into the neuroprotection effects and mechanism of thiazolidinedione pioglitazone in both in vitro and in vivo MPP+/MPTP induced PD models. In vivo experimental results showed that oral treatment of pioglitazone resulted in significant improvements in behavior symptoms damaged by MPTP and increase in the survival of TH positive neurons in the pioglitazone intervention groups. In addition, oral treatment of pioglitazone increased the expression of peroxisome proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…For this reason, we have tested in a cell model of DS the effects of a thiazolinedione, namely PGZ, a PPAR-γ agonist, which stimulates PGC-1α expression. PGZ plays a neuroprotective role in dopaminergic neurons in both in vitro and in vivo PD models (Wang et al, 2017), which was associated with PGC-1α induction and the regulation of proteins involved in mitochondria function (Wang et al, 2017). We intentionally used low doses of the drugs because both metformin and PGZ are known to inhibit respiratory complex I when used at high concentrations (Brunmair et al, 2004; Ghosh et al, 2007; Garcia-Ruiz et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, we have tested in a cell model of DS the effects of a thiazolinedione, namely PGZ, a PPAR-γ agonist, which stimulates PGC-1α expression. PGZ plays a neuroprotective role in dopaminergic neurons in both in vitro and in vivo PD models (Wang et al, 2017), which was associated with PGC-1α induction and the regulation of proteins involved in mitochondria function (Wang et al, 2017). We intentionally used low doses of the drugs because both metformin and PGZ are known to inhibit respiratory complex I when used at high concentrations (Brunmair et al, 2004; Ghosh et al, 2007; Garcia-Ruiz et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial fission is implicated in the cell death through a pathway that involves caspase activation 71 , and Mitochondrial fission 1 protein (Fis1) is considered essential for mitochondrial fission 72 . Overexpression of Fis1 caused increase of mitochondrial fragmentation, which conducted to apoptosis or triggered autophagy 73 , 74 , and neuroprotective effects are correlated with inhibition of Fis1 75 .…”
Section: Discussionmentioning
confidence: 93%
“…In the 6-hydroxydopamine (6-OHDA)-induced rat model of PD, the cytosolic and nuclear protein levels of Nrf2 are markedly reduced, which is accompanied by facilitated DRP1-mediated mitochondrial fission [ 85 ]. In the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) model of PD, the expression levels of FIS1 are elevated concomitantly with the reduced levels of MFN2 and Nrf2 [ 86 ], although Mendes et al [ 87 ] have reported that MPTP transiently increases the expression of Nrf2 and parkin. Thus, it is likely that reduced Nrf2 expression/activity may be relevant for mitochondrial fragmentation and impaired mitophagy in PD ( Figure 4 and Table 2 ).…”
Section: Nrf2 Mitochondrial Dynamics and Mitophagy In Neurologicmentioning
confidence: 99%